Peran Kepala Sekolah terhadap Peningkatan Mutu Pembelajaran Sekolah Dasar Negeri di Kendari - Hijayanti Dwi Kartini; Halistin Halistin; Samrin Samrin; Badarwan Badarwan (IAIN Kendari, 2022)
This study aims to determine the principal’s roles as efforts in improving the quality of education at one of the public elementary schools in Kendari, Southeast Sulawesi. Data collection was carried out in the form of interviews, observation and documentation using a qualitative research design. Analysis of research data consisted of data reduction, data presentation and data verification. The data validity test was carried out through observation and triangulation techniques. The results of the study show that the role of school principals in improving the quality of learning in schools has been maximized starting from efforts to increase teacher professionalism, including by providing training, conducting teacher assessments and evaluations, conducting individual and group coaching (joint meetings) and establishing good cooperative relations in between teachers, students and the entire school community in general. In addition, facilities and infrastructure are increasingly being improved to fulfill the main needs of schools that support the quality of learning.Keywords: Principal’s roles, education quality, elementary school